Task-based Pedagogies in Iran: The Relationship between Oracy and Literacy. (December 2020) - Shakhsi Dastgahian, Elahe; Turner, Marianne; Scull, Janet
Despite the recent emphasis on oral English language proficiency in the Iranian education system, the teaching of oral communication remains a challenge for secondary school English language teachers. In this article, we suggest that this, in part, relates to the continued emphasis on literacy practices. The article explores the approach taken by three Iranian junior high school English language teachers to teaching oracy during a summer school task-based intervention. Data were gathered through observations and interviews, and third generation activity theory from Engeström (1996; Engeström 2001) was used to analyse teachers' practices. Findings revealed that, while trialling aspects of task-based pedagogies, the teachers' attention to oracy increased. However, they retained a strong traditional focus on literacy teaching, which had an effect on their approach to oracy and also appeared to constrain their movement towards less-controlled spoken language. This small-scale study offers insights into approaches to oracy teaching while employing task-based pedagogies in foreign language contexts like Iran. In this context, English literacy has been the historical focus, the Roman alphabet is new for the students, and there is often limited exposure to oracy practices outside the classroom context (Sadeghi and Richards, 2015).